Studies of haematological parameters of Oreochromis niloticus exposed to Cadmium Chloride (CdCl2, 2H2O) - Parekh, Hetalben M; Tank, Shantilal K (International Journal of Environment, 2015)
The effects of Cadmium Chloride on the specimen Nile tilapia (Oreochromis niloticus) were examined for evaluation as acute toxicity for 96 hours. From the recorded information using Probit Analysis-Finney Method [Log-normal Distribution] the results revealed the mean 96 hour LC50 value to be 3.5095 mg/L indicating very high potential toxicity. Also derived value for mean NOEC=0.9062 mg/L defined safe limits of cadmium. In order to assess the effect of prolonged exposure of low concentration of cadmium haematological assessment was made after 24 hour, 7 days and 15 days of exposure. The study of haematological parameters demonstrated significant reduction in Red Blood Cell count, Haemoglobin, Haematocrit and Mean Corpuscular Haemoglobin Concentration (MCHC) and Mean Corpuscular Haemoglobin (MCH); while elevation was reported in Mean Corpuscular Volume (MCV). Leading to conclusion that mature RBCs are destructed and the erythrocyte production is inhibited due to reduction of haemesynthesis. Stimulation of erythropoiesis is considered as one of the reasons for decrement in values of Haemoglobin, Haematocrit and RBC count. DOI: http://dx.doi.org/10.3126/ije.v4i2.12631 International Journal of Environment Vol.4(2) 2015: 116-127